Ring Expansions Within the Gold‐Catalyzed Cycloisomerization of O‐Tethered 1, 6‐Enynes. Application to the Synthesis of Natural‐Product‐like Macrocycles. Issue 5 (9th November 2012) - Simonneau, Antoine; Harrak, Youssef; Jeanne‐Julien, Louis; Lemière, Gilles; Mouriès‐Mansuy, Virginie; Goddard, Jean‐Philippe; Malacria, Max; Fensterbank, Louis
<x xml:space="preserve">Abstract</x> Goldenyne: O‐tethered 1, 6‐enynes that contain a strained ring at the 3 position can cycloisomerize upon cationic gold(I) catalysis through a ring‐expansion process. A two‐step sequence allows the transformation of the cyclized compounds into ketomacrolactones, which are reminiscent of natural products.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>